THE EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL IN IMPROVING STUDENTS' CRITICAL THINKING SKILLS AND LEARNING OUTCOMES - Surya Octavianus Simbolon; Haryono Haryono; Decky Avrilianda; Rafika Bayu Kusumandari (RADJA PUBLIKA, 2026)
This study aimed to examine the effectiveness of the Problem Based Learning (PBL) model in improving students' critical thinking skills and learning outcomes. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research was conducted in [name of school] involving two classes, namely an experimental class and a control class. The experimental class received instruction through the PBL model, while the control class was taught through conventional learning. Data were collected through critical thinking tests and learning outcome tests administered in the form of pretest and posttest, supported by observation and documentation. Data analysis included descriptive statistics, prerequisite tests, independent sample t-test, N-gain analysis, and effect size analysis. The findings indicated that students in the experimental class experienced a more substantial improvement than those in the control class. PBL encourages students to actively engage in identifying problems, discussing ideas, analyzing information, and formulating solutions based on real contexts. These processes contributed to the development of critical thinking and deeper conceptual understanding. Therefore, Problem Based Learning can be considered an effective instructional alternative to enhance students' critical thinking skills and learning outcomes.